Fight back : Aids Coalition To Unleash Power. (Utrecht Amsterdam : ACT UP Utrecht ACT UP Amsterdam, 1993)
Fonds Suzan Daniel (FSD)
Periodiciteit : tweemaandelijks?
Redactie : PB 19052, 3501 DB Utrecht
Nederlands
Periodiek